A Juridical Analysis of the Role of Incoterms 2000 in Risk Allocation Concerning Non-Tariff Barriers in Export-Import Transactions - Michelle Christie (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The objective of this study is to analyze the role of Incoterms 2000 in the allocation of risks arising from non-tariff barriers in export-import transactions. As a form of international trade policy, non-tariff barriers manifest in various ways during the execution of transactions, such as shipment delays, detention, or rejection of goods in the destination country. These conditions not only impact technical aspects but also give rise to legal issues in the contractual relationship between the exporter and the importer. This study employs a normative legal research method using a legislative and conceptual approach. The results of the study indicate that Incoterms 2000 play a crucial role in determining risk allocation through the establishment of the point of risk transfer. With the provisions of Incoterms in place, it becomes clear which party is responsible should obstacles arise during the execution of a transaction. Therefore, selecting the appropriate type of Incoterms is vital to providing legal certainty and minimizing the potential for disputes in international trade in the future